(untitled) (Global Journal of Management and Business Research, 2014)
The economic development of a nation remains paramount to any government and this can be achieved through the activities of macromarketing. The study conceptually and empirically showed how the activities of macromarketing by firms in the area of retail, telecommunication and aviation had led to improvement in per capita income, standard of living, job creation, alleviation of poverty, increase in government revenues, improved infrastructural facilities. Government is required to encourage all sector in economy to act responsibly and ensure that both firms and government act in the interest of the nation.